The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.5039/agraria.v1i1a127
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação genética de bovinos Guzerá utilizando-se a produção de leite e de gordura no dia do controle

Abstract: Dados referentes a 467 lactações e 5.604 controles de bovinos da raça Guzerá, controladas entre 1987 e 2004, foram utilizados com objetivos de se estimar os parâmetros genéticos e predizer os valores genéticos para a produção de leite (PLDC) e de gordura (PGDC) no dia do controle, e comparar a classificação dos animais por estimativas obtidas mediante análises unicaracterísticas. A PLDC e PGDC foram analisadas através de um modelo animal, em análises unicaracterísticas, considerando-se as quatro primeiras lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The phenotypic LMY and DIM performances observed in this study were close to those observed in other studies with the Guzerat breed (Cobuci et al, 2000;Martinez et al, 2000;Cruz et al, 2006).…”
Section: Productive and Reproductive Data Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…The phenotypic LMY and DIM performances observed in this study were close to those observed in other studies with the Guzerat breed (Cobuci et al, 2000;Martinez et al, 2000;Cruz et al, 2006).…”
Section: Productive and Reproductive Data Analysissupporting
confidence: 91%
“…In the analysis of milk yield, some authors have used comparable statistical models, but without considering the inbreeding coefficient as a covariate (Cobuci et al, 2000;Cruz et al, 2006;Peixoto et al, 2006). In the present study, since there were a great number of inbred animals in the herd, the inclusion of the inbreeding coefficient was necessary for the adjustment of the estimated breeding values of highly inbred cows or bulls with highly inbred daughters.…”
Section: Productive and Reproductive Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, whereas some animals have good milk yield persistence, others reduce, or even cease, production early in lactation. Cruz et al (2006), who also studied TDMY in Guzerat cows, observed a similar trend of variance components during the early period of lactation, including the observation of higher heritabilities compared to midlactation. However, the range of heritability values was wider (from 0.03 in the fifth month to 0.29 in the eighth and tenth months).…”
Section: Discussionmentioning
confidence: 55%